Phosgene-Induced acute lung injury: Approaches for mechanism-based treatment strategies - Cao, Chao; Zhang, Lin; Shen, Jie (Frontiers in Immunology, 2022)
Phosgene (COCl2) gas is a chemical intermediate of high-volume production with numerous industrial applications worldwide. Due to its high toxicity, accidental exposure to phosgene leads to various chemical injuries, primarily resulting in chemical-induced lung injury due to inhalation. Initially, the illness is mild and presents as coughing, chest tightness, and wheezing; however, within a few hours, symptoms progress to chronic respiratory depression, refractory pulmonary edema, dyspnea, and hypoxemia, which may contribute to acute respiratory distress syndrome or even death in severe cases. Despite rapid advances in medicine, effective treatments for phosgene-inhaled poisoning are lacking. Elucidating the pathophysiology and pathogenesis of acute inhalation toxicity caused by phosgene is necessary for the development of appropriate therapeutics. In this review, we discuss extant literature on relevant mechanisms and therapeutic strategies to highlight novel ideas for the treatment of phosgene-induced acute lung injury.